CARDIAC VALVE PROSTHESIS «MEDENG-2»: 10 YEARS EXPERIENCE OF CLINICAL APPLICATION Vavilov P.A. - P. A. Vavilov (Вестник трансплантологии и искусственных органов, 2010)
In our department from December 1998 to 2009 have been performed 1028 operations with use of prosthesises «MedEng-2»: aortic valve replacement (AVR) – 494, mitral valve replacement (MVR) – 351 and double valves mitral and aortic replacement (DVR) – 183. Remote results are tracked at 76% (719) patients. The 10-years survival rate has made 4532 patient-years of them 3146 pats.-years (86,4%) for AVR, 2530 (82,4%) for MVR and 836 (82,9%) for DVR. Mechanical dysfunctions of artificial valves were not. Freedom from a thrombosis, endocarditis and reoperations at AVR has made 98,7; 97,6; 97,1% accordingly. From embolism complications – 97,5%. For MVR freedom from thrombosis – 96,9%, endocarditis – 97,7%, from reoperations and embolism complications of 99,1 and 91,2%. Freedom from throm- bosis and endocarditis at DVR 100 and 97,4% accordingly. From embolism complications and reoperations – 97,5%. The analysis of 10-years results of replacements prosthetics valves «MedEng-2» has shown its good haemody- namic qualities and satisfactory results both in the nearest, and in the remote terms after operation.